Boundary Value Analysis Techniques for Testing Geographic Information System Applications for Public Facilities - Idmayanti, Rika; Meidelfi, Dwiny; Erianda, Aldo; Sukma, Fanni; Zazkia, Rahmi (SOTVI, 2022)
The Geographic Information System for Public Facilities is a system that makes it easier for the public to search and find locations. The more people use this system, the more problems will arise. Because people still use the manual method, namely by asking about the location of public facilities in the surrounding community. This is very ineffective and accurate. Therefore, a public facility information system was built using CI 3, Java, and PHP in the form of android. The method used in this development system is the waterfall method. With this GIS, the public can search for the location of public facilities, find public facilities, and provide a route to the location using the Tracking process to find out where the current position is.